Threatened Wildlife of the Twin Lakes Balinsasayao and Danao Natural Park, Negros Oriental, Philippines - Dolino, Cynthia N.; Cariño, Apolinario B.; Cadeliña, Angelita M. (Silliman Journal, 2022)
The Twin Lakes of Balinsasayao and Danao of southeastern Negros constitute an extensive tropical rainforest ecosystem and one of the centers of great biological diversity on Negros Island. They are a part of the 133,000 ha Philippine National Oil Company (PNOC) Geothermal Reserve. The lakes and forest ecosystems are refuges to the 180 species of dipterocarp and non-dipterocarp trees, 113 species of birds, 27 mammals, and 49 amphibians and reptiles. Currently, the Twin Lakes have been officially declared as a Natural Park with some of the unique mammals, birds, amphibians, and reptiles in threatened status. The vertebrate fauna having the most threatened species are the birds with 17 globally threatened species. The mammals have 11 threatened species that are under different levels of threat. The amphibians have 5 threatened species while the reptiles have two lizards and one snake that are threatened. Habitat loss and degradation coupled with discrete hunting, collection and harvesting of aquatic and forest resources for subsistence, commercial, ornamental, pet, or zoo trade are putting an increasing pressure on threatened and non-threatened plant and animal species in the Twin Lakes area. Long-term conservation program for keystone threatened plant and animal species is essential for the preservation of the remaining forest and its wildlife.